2000
DOI: 10.1186/bcr91
|View full text |Cite
|
Sign up to set email alerts
|

P53 autoantibodies in 1006 patients followed up for breast cancer

Abstract: Serial plasma samples from 1006 patients with breast cancer revealed: (i) no correlation of p53 autoantibody status with disease status at the time of sample collection, or with menopausal status at time of primary diagnosis of breast cancer; (ii) 155 out of 1006 (15%) of patients were positive for p53 autoantibodies, and these patients tended to have a persistent autoantibody status throughout follow up, irrespective of disease behaviour; and (iii) where a negative autoantibody status was found at primary dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…In breast cancer, particular interest in such correlations has focused on anti-53 autoantibodies, where some studies observed a correlation between poor prognosis and increased levels of anti-53 autoantibodies (70,71), although these results could not always be confirmed by others (72). It may, therefore, seem surprising that the favorable prognosis of MCB correlates with anti-actin autoantibodies.…”
Section: Discussionmentioning
confidence: 75%
“…In breast cancer, particular interest in such correlations has focused on anti-53 autoantibodies, where some studies observed a correlation between poor prognosis and increased levels of anti-53 autoantibodies (70,71), although these results could not always be confirmed by others (72). It may, therefore, seem surprising that the favorable prognosis of MCB correlates with anti-actin autoantibodies.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, in certain patients, an ongoing stimulus might trigger a progressive immune response over time. Although this effect might be counteracted by immunosuppression as a side effect of chemotherapy [24, 31], our results render it likely that the increased prevalence of confirmed anti-p53 positives in advanced stages of breast cancer mirrors the development of anti-p53 titers during the course of disease.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, we do not assume that this marker will be clinically useful in identifying high-risk patients. Furthermore, a recently published follow-up study [31]with a similarly low overall incidence of anti-p53 autoantibodies (15%) in breast cancer, failed to show an association with the stage of the disease, and revealed a high stability of the anti-p53 status in the follow-up of a single patient. In view of the accepted prognostic value of aberrant p53 [8, 9]and the link between aberrant p53 and the development of anti-p53 [24], one would expect higher rates of p53 accumulation and consecutively anti-p53 positivity in recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, autoantibodies directed against p53 correlate with poor prognosis. [19][20][21] Likewise, autoantibodies associated with paraneoplastic syndromes have been correlated with poor prognosis and are thought to lead to fatal neurologic disorders. 22,23 Autoantibodies correlated with prolonged survival of tumor patients are rare and to the best of our knowledge of low specificity.…”
Section: Discussionmentioning
confidence: 99%